O contramovimento dos produtores de orgânicos do Assentamento Agroana Girau de Poconé – MT : abordagens alternativas para o desenvolvimento - Leite, Diogo Barbosa (2019)
Discussions about the concept of development were striking for several areas of science, especially economics. Diverse currents, approaches and theories, in both positive and normative aspects, had the purpose of explaining the concept, each one from its own perspectives. With this, the modernizing actions of the last century provoked intense transformations in society, provoking a continuous revision of the concept. One of these transformations occurred in agriculture, through the Green Revolution and the use of the technological package, appropriated on a large scale by the nations. However, this revolution provoked social, economic and environmental distortions, corroborating the emergence of new production practices, based on defense movements for organic and agroecological crops. Thus, this study had as study subjects the family farmers of the settlement Agroana Girau, from Poconé-MT, who cultivate organic products. From this, the starting point was the guiding question: after the transition period from conventional to organic management, has this alternative been a promoter of the development of the families of the Agroana Girau settlement? The general objective was to analyze the dynamics of the development of organic production in the community after the transition period of conventional management, followed by the specific objectives: describe the performance of organic farmers in the community, the way of organization and marketing forms used; characterize the organic mode of production employed; to verify in the family farmers the main results obtained from the transition period, relating them to the development theories presented. Regarding the methodology, the research is classified as exploratory and descriptive, with a qualitative approach with data collection performed through semi-structured interviews. Interviews were conducted with seven owners who cultivate organic products, as well as direct observation in the community. The study cut is transversal, since the data were collected in December 2018. The collection instrument was a script composed of twenty-six questions, divided into three blocks of questions. Among the techniques of data analysis, content analysis and triangulation were used. The results indicate that the producers act in the form of a network, have an intense subjective component to act and stay in the activity, besides adopting a collective marketing strategy, through sale in short circuits. In addition, UFMT has played a relevant role both in the transition process from conventional to agroecological management and in promoting an institutional environment conducive to the development of the activity. Farmers use an agro-ecological-based organic activity by providing environmental as well as social concepts. There were indications of actions related to the endogenous development of the community, such as the use of local knowledge as a plumber of innovations. The research revealed that agroecological activity has presented itself as an interesting niche for these decapitalized family farmers. Finally, it was implicitly verified that collective action supported the establishment of common ties and feelings among farmers. The idea of countermovement as a product was implicitly verified if its economic, social and environmental performance, which can contribute to the capacity for emancipation, serving as a basis for political and productive support. Through this agro-ecological network the producers share knowledge, exchange learning, maintain common values and re-signify the organic market of the region.